PENGARUH POSISI VACUUM GATE TERHADAP WAKTU INFUSE PADA PROSES VACUUM ASSISTED TRANSFER MOLDING - Lazuardi Rahmadhani; Ahmad Syuhri; Aris Zainul Muttaqin (STATOR: Jurnal Ilmiah Mahasiswa Teknik Mesin, 2018)
Vacuum assisted resin transfer molding is one of the methods making products where resin as matrix sucked with pressure vacuum in moulding with tranpaent bagging.The result product of vacuum assisted resin transfer molding thinner than the hand lay up method but needs longer process of infuse. Variation position vacuum gate placed in three position different 60 %, 80% and 100% of the mold lenght and vacuum pressure -0.6 bar, -0.8 bar and -1.0 bar. Spending time the process infuse for 12 minutes 48 seconds at the vacuum gate be at 80 % of the total mold length and vacuum pressure of -1.0 bar. With varying vacuum pressure and the position vacuum gate showed engineering successful in this area to produce goods process a shorter. Keywords: Vacuum Assisted Resin Transfer Molding, Vacuum Gate , Time Infusion.